The Pleasure of Architecture and the Tenderness of the Landscape (diségno, 2024)
After a first failed attempt in 1976, in May 1982, within the Grands Projets program promoted by François Mitterrand, a competition was announced for the Parc de la Villette on an area of 50 ha in a working-class neighborhood in the north-east of Paris that had hosted the slaughterhouses. [read more]